The Telemetry Control System on Omni wheel Enemy Infiltrator Robot Based on Internet of Things (IoT) - Syabana, Badrus Umam; Yulisusianto, Gatut; Setiawan, Riyant Budi (Jurnal Elkasista, 2021)
The development of sophisticated technology in the era of the industrial revolution 4.0, namely the collaboration between automation technology and the internet, causing changes in the combat and reconnaissance model to be remotely. The internet of things based omni wheel robot is divided into three module units, the main module, the data processing module, and the drive module. This concept uses a telemetry control system that is integrated with computers and the internet for data processing. The omni wheel robot is used in urban terrain for autonomous mobile surveillance operations and webcam monitoring via a web server. The omni wheel robot is designed to use four omni wheel controls and a trajectory as the main autonomous drive for the robot, the raspberry pi 3 is a microcontroller for processing programs on the robot and the webcam is used to take pictures of the terrain the robot passes through. All controls on the omni wheel robot use a telemetry system by using Wi-Fi internet network access remotely to minimize losses for TNI soldiers’ personnel in carrying out reconnaissance tasks.